Rapid, simple, and simultaneous electrochemical determination of cadmium, copper, and lead in Baijiu using a novel covalent organic framework based nanocomposite - Yu, Liangyun; Zhang, Jingjing; Li, Jiajun; Sun, Liangju; Zhang, Qi; Yang, Bairen; Huang, Mingquan; Xu, Baocai (Frontiers in Chemistry, 2024)
It is of great significance to develop a simple and rapid electrochemical sensor for simultaneous determination of heavy metal ions (HMIs) in Baijiu by using new nanomaterials. Here, graphene (GR) was utilized to combine with covalent-organic frameworks (COFs) that was synthesized via the aldehyde-amine condensation between 2, 5-dimethoxyterephthalaldehyde (DMTP) and 1, 3, 5-tris(4-aminophenyl) benzene (TAPB) to prepare a new GR/COF DPTB /GCE sensor for electrochemical sensing multiple HMIs. Compared with the glass carbon electrode (GCE), GR/GCE and COF DPTB /GCE, the developed sensor exhibited excellent electrochemical analysis ability for the simultaneous detection of Cd 2+ , Pb 2+ and Cu 2+ owing to the synergistically increased the specific surface area, the periodic porous network and plenty of effective binding sites, as well as the enhanced conductivity. Under the optimized experimental parameters, the proposed sensor showed good linearity range of 0.1-25 μM for Cd 2+ , and both 0.1-11 μM for Pb 2+ and Cu 2+ with the detection limits of Cd 2+ , Pb 2+ and Cu 2+ being 0.011 μM, 8.747 nM and 6.373 nM, respectively.Besides, the designed sensor was successfully applied to the simultaneous detection of the three HMIs in Baijiu samples, suggesting its good practical application performance and a new method for the rapid detection of HMIs being expended.